2018
DOI: 10.1103/physrevfluids.3.013601
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the impact energy on the pattern of blood drip stains

Abstract: The maximum spreading diameter of complex fluid droplets has been extensively studied and explained by numerous physical models. This research focuses therefore on a different aspect, the bulging outer rim observed after evaporation on the final dried pattern of blood droplets. A correlation is found between the inner diameter, the maximum outer diameter, and the impact speed. This shows how the drying mechanism of a blood drip stain is influenced by the impact energy, which induces a larger spreading diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…It describes how a bullet atomizes blood; how the impact of a fist on a moving face squeezes and splashes blood; how airborne droplets move along trajectories curved by gravity and slowed by drag; and how drops spread, wick, and dry onto materials as complex as fabrics. Only recently, peer-reviewed fluid dynamic studies have started to uncover the complex physics underlying BPA [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. The governing equations of fluid dynamics are called the Navier-Stokes equations; they are the expression of Newton's second law for fluids.…”
Section: Proposed Direction 1: Better Understand the Physics Associated With Bpamentioning
confidence: 99%
“…It describes how a bullet atomizes blood; how the impact of a fist on a moving face squeezes and splashes blood; how airborne droplets move along trajectories curved by gravity and slowed by drag; and how drops spread, wick, and dry onto materials as complex as fabrics. Only recently, peer-reviewed fluid dynamic studies have started to uncover the complex physics underlying BPA [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72]. The governing equations of fluid dynamics are called the Navier-Stokes equations; they are the expression of Newton's second law for fluids.…”
Section: Proposed Direction 1: Better Understand the Physics Associated With Bpamentioning
confidence: 99%
“…Brutin et al have demonstrated that red blood cells will affect the dried bloodstain pattern [39]. Besides, Smith et al found a correlation between dried bloodstain pattern and droplet impact energy [40]. These studies indicate that particles that simulate red blood cells need to be added to the BS used for bloodstain pattern analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The DOD process was modeled and analyzed via the drying of droplets. , Until now, DOD studies were investigated concerning the geometric properties of the droplet (volume, diameter, etc. ), viscosity, surface tension, density, and surface energy and roughness. Also, the impacts of pH and surfactant on the drying pattern were analyzed by using the various droplet and substrate characteristics. Another example is the blood/surrogate blood droplet evaporation in biological applications with the assumption of the blood droplets as the suspension-laden ones that were modeled with respect to the humidity effect, crack formation, , surface roughness and wettability, relation between the number of cracks and droplet diameter, evaporation rate, and impact energy . Besides the aforementioned cases, we have been working with droplet evaporation with nanoparticle-laden droplets by investigating the flow regime and deposition patterns of binary mixtures, , disk-to-dual ring deposition, , and impacts of (i) surfactants on the droplet deposition and (ii) multisized nanoparticles .…”
Section: Introductionmentioning
confidence: 99%